High prevalence of late presentation of ART-naïve perinatally infected children for care in Pune, India. Issue 11 (1st November 2020) - Nimkar, Smita; Kinikar, Aarti; Chavan, Amol; Sangle, Shashikala; Rewari, Bharatbhushan; Gupta, Amita; Mave, Vidya; Marbaniang, Ivan
ABSTRACT: Delayed presentation to care of perinatally infected children in India continues to be a hindrance to achieving the "end pediatric HIV by 2020" goal. In this study, we characterize this issue by describing the prevalence, risk factors and temporal trends of delayed presentation to care of perinatally infected, antiretroviral therapy (ART) – naïve children using programmatic data from a tertiary care center in western India. Delayed presentation was defined as children presenting in moderate or severe WHO immunodeficiency categories. Of 269 children eligible for inclusion in the analysis, the median age at presentation was 4 years (IQR: 3–6 years) and prevalence of delayed presentation was 52%. Multivariable logistic regression identified domicile distance ≥20km from the ART center (OR: 2.2, 95% CI: 1.02–4.7) to be a risk factor for delayed presentation. An inverse association with increasing age (OR: 0.8, 95% CI: 0.7–0.9) was also seen. The proportion of children with delayed presentation between 2006 and 2016 remained unchanged ( p  = 0.36), although the median age at presentation over the same time period increased significantly ( p  < 0.001). Our results indicate the urgency of identifying strategies to improve linkage of perinatally infected ART-naïve children to care, earlier than what is currently observed.